2010
DOI: 10.1007/s10549-010-0958-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Declining melatonin levels and MT1 receptor expression in aging rats is associated with enhanced mammary tumor growth and decreased sensitivity to melatonin

Abstract: Serum melatonin (MLT) levels have been reported to diminish significantly by the 5th and 6th decades of life as the incidence of breast cancer increases. Given MLT's anti-cancer activity, we hypothesize that age-related decline in pineal MLT production leads to enhanced breast cancer development and growth as women age. In this study, we sought to determine whether the growth of tissue-isolated mammary tumors in young, adult, and old female Buffalo rats relates to the age-related changes in MLT and its MT1 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
1
21
3
Order By: Relevance
“…A recent cohort study of postmenopausal women has also revealed that an increased concentration of urinary 6-sulfatoxymelatonin (aMT6s), the major metabolite of MLT, is statistically significantly associated with a lower risk of developing breast cancer [9]. These observations are further supported by the fact that MLT production gradually declines with advancing age, with MLT levels reported to be low in elderly individuals, associated with ER-positive breast cancer and linked with enhanced tumor growth in rats [10][11][12].…”
Section: Introductionmentioning
confidence: 93%
“…A recent cohort study of postmenopausal women has also revealed that an increased concentration of urinary 6-sulfatoxymelatonin (aMT6s), the major metabolite of MLT, is statistically significantly associated with a lower risk of developing breast cancer [9]. These observations are further supported by the fact that MLT production gradually declines with advancing age, with MLT levels reported to be low in elderly individuals, associated with ER-positive breast cancer and linked with enhanced tumor growth in rats [10][11][12].…”
Section: Introductionmentioning
confidence: 93%
“…Since Ca 2 þ seems to be a crucial regulator of the cell cycle necessary for proper proliferation (Bertolesi et al, 2002;Gray et al, 2004;Naziroğlu et al, 2012;Wang et al, 2000), the associated reduction of free [Ca 2 þ ] i observed in our experiments supports the clue that melatonin may contribute to the decline of proliferation also disturbing internal Ca 2 þ homeostasis. The G-protein-coupled melatonin MT1 receptors are expressed in MCF-7 cells (Girgert et al, 2009;Hill et al, 2011b;Jablonska et al, 2013;Jawed et al, 2007;Rich et al, 1999) and, via the inhibition of adenylate cyclase activity (Jablonska et al, 2013;Jawed et al, 2007), their activation leads to the decrease of adenosine 3 0 , 5 0 -cyclic monophosphate (cAMP) synthesis. Considering that in MCF-7 melatonin affected cell functionality by a significant depletion of ATP levels (Margheri et al, 2012), we propose that the decrease of cAMP, leading to a decrease of PKA activity and channel phosphorylation, can be considered a crucial mechanism involved in the reduction of L-and T-type Ca 2 þ currents (Mahapatra et al, 2012;Novara et al, 2004;Sundelacruz et al, 2009), further stressing the evidence that Ca 2 þ channels are a target by which melatonin can modulate cell proliferation.…”
Section: Ctrmentioning
confidence: 99%
“…Understanding the health-relevant impact of LAN on L1 activity in normal cells is an important next step in our research, as it is directly relevant to aging and age-associated diseases. It is established that melatonin production and its receptor expression decline with age, 63 suggesting the possibility of an increase in L1-induced damage with age. As previously mentioned, genomic instability is an underlying cause of most cancers.…”
mentioning
confidence: 99%